Flow dynamics at the origin of thin clayey sand lacustrine turbidites: Examples from Lake Hazar, Turkey. Issue 7 (23rd June 2017) - Hage, Sophie; Hubert‐Ferrari, Aurélia; Lamair, Laura; Avşar, Ulaş; El Ouahabi, Meriam; Van Daele, Maarten; Boulvain, Frédéric; Ali Bahri, Mohamed; Seret, Alain; Plenevaux, Alain
Abstract: Turbidity currents and their deposits can be investigated using several methods, i.e. direct monitoring, physical and numerical modelling, sediment cores and outcrops. The present study focused on thin clayey sand turbidites found in Lake Hazar (Turkey) occurring in eleven clusters of closely spaced thin beds. Depositional processes and sources for three of those eleven clusters are studied at three coring sites. Bathymetrical data and seismic reflection profiles are used to understand the specific geomorphology of each site. X‐ray, thin sections and CT scan imagery combined with grain‐size, geochemical and mineralogical measurements on the cores allow characterization of the turbidites. Turbidites included in each cluster were produced by remobilization of surficial slope sediment, a process identified in very few studies worldwide. Three types of turbidites are distinguished and compared with deposits obtained in flume studies published in the literature. Type 1 is made of an ungraded clayey silt layer issued from a cohesive flow. Type 2 is composed of a partially graded clayey sand layer overlain by a mud cap, attributed to a transitional flow. Type 3 corresponds to a graded clayey sand layer overlain by a mud cap issued from a turbulence‐dominated flow. While the published experimental studies show that turbulence is damped by cohesion for low clay content, type 3 deposits of this study show evidence for a turbulence‐dominated mechanism despite their high clay content. This divergence may in part relate to input variables, such as water chemistry and clay mineralogy, that are not routinely considered in experimental studies. Furthermore, the large sedimentological variety observed in the turbidites from one coring site to another is related to the evolution of a sediment flow within a field‐scale basin made of a complex physiography that cannot be tackled by flume experiments.